Tlingit grave totems and totem poles, Kake, Alaska, 1895 - Winter, Lloyd Pond, E. Percy
Tlingit grave totems and totem poles; at far left is eagle on grave, pole on left has spotted frog, pole in center has man in hat at top, pole on right has bear. Caption on image: 288. Totem poles, Kake, Alaska. Copyright 1895 by Winter & Pond